A Treat towards an Artist’s Psyche: A Psychoanalytical Reading of ‘Red’ by John Logan - Sajed Hosseini (International Journal of English Language and Translation Studies, 2020)
The essence of human psyche as a primary subject of psychoanalytical discussions was in the center of attentions throughout the nineteenth and twentieth centuries. Thereupon, the investigations of various human psyche lead to the understanding of the relation between the conscious and the unconscious. In other words, what people do is done instinctively as a reaction toward their unconscious. On the contrary, human beings were not cognizant of unconscious’ complexity; the directory of individual lives is interrelated to choices that are made in an out-of-reach aspect of mind, which does not always make a sense. Psychoanalysis, as a nonmedical observation of human mind, zooms in on various ways of interpretation of an individual’s psyche. For instance, a famous play by John Logan entitled Red, written in 2009, appears to picture different aspects of an artist out of its characters’ psyche while distinctively make conversation within the play. This paper’s intention is to provide a reading Rothko, protagonist of Red, with having eye on the features discussed by the theories of psychoanalysis. The analysis illustrates the complexions of individuals’ psyche interlocked with different circumstances and situations.